Auxiliary functional group diffusion dialysis membranes for acid recovery. Issue 21 (3rd July 2022) - Cheng, Congliang; Shen, Hai Yang; Gong, Yifei; Chen, Wei; Li, Ping
Abstract: Anion exchange membranes with auxiliary group were prepared by quaternized brominated polyphenylene oxide and hydroxyl tertiary amine. The basic properties of the membrane were characterized using ion exchange capacity, water content, linear expansion rate, thermal weight loss, acid resistance and microstructure of membrane, and so forth. The application of the membrane in the recovery of acid by diffusion dialysis (DD) was also explored showing the excellent comprehensive performance where the dialysis coefficient of HCl ( U H+ ) increases from 0.011 to 0.033 m/h, but the separation factor (S) is over 35.6. Comparing with the commercial DF‐120 membrane (0.009 m/h, 18.5), the auxiliary hydroxyl with group can improve DD performance of the membrane markedly. Our finding shows the membranes with auxiliary hydroxyl group developed here have great potential for high‐efficiency acid recovery by diffusion dialysis. Abstract :